IMPLEMENTATION OF SUB-DISTRICT INTEGRATED ADMINISTRATIVE SERVICES (PATEN) IN CANDI SUB-DISTRICT, SIDOARJO REGENCY - Asmunif; Rodiyah, Isnaini (Journal of Geography, Regional Planning and Development, 2024)
General Background: The effectiveness of public administration in delivering services is a critical factor in governance. The quality of sub-district administrative services plays a crucial role in ensuring that citizens have access to efficient and effective government support. Specific Background: Integrated sub-district administrative services (PATEN) in Candi District, Sidoarjo Regency, have been established to improve public service delivery. However, the optimization of such services remains a challenge, particularly in terms of communication, resources, disposition, and bureaucratic structure. Knowledge Gap: While there is significant literature on administrative service delivery, limited studies have specifically focused on the implementation of integrated sub-district services in Indonesia. Furthermore, there is a lack of comprehensive analysis that considers the four key aspects of implementation: communication, resources, disposition, and bureaucratic structure. Aims: This study aims to analyze the implementation of integrated sub-district administrative services in Candi District, Sidoarjo Regency, by evaluating the effectiveness of communication, resource utilization, employee disposition, and bureaucratic structure. Results: The findings indicate that communication within the Candi District Government is optimal, with both direct and indirect communication methods used in service delivery. However, the resources available are not fully optimized, particularly in terms of service space. The disposition of employees is optimal, as they are able to clearly understand and follow leadership instructions. The bureaucratic structure is also optimal, with clear procedures and standard operating procedures (SOPs) in place for delivering services. Novelty: This study offers a novel approach to evaluating integrated administrative services by combining the four implementation factors (communication, resources, disposition, and bureaucratic structure) in a specific regional context, which has been underexplored in existing research. Implications: The findings suggest that while communication, disposition, and bureaucratic structure are optimal, there is a need to improve resource allocation, particularly in terms of physical space, to further enhance the effectiveness of administrative services in Candi District.